Using a 3-Dimensional Industrial Vehicle Model on Arbitrary Ground Geometries. Issue 31 (2018) - Oei, Marius; Sawodny, Oliver
Abstract: Dynamic driving assistance functions are beginning to enjoy popularity in the sector of industrial vehicles. Many such functions rely on a precise model of the vehicle dynamics. In consideration of the usage scenarios (e.g. intralogistics) and specific properties of industrial vehicles, common simplified dynamics models for passenger cars and highway trucks are not suitable for an accurate description of the vehicle behavior. In this work the relevant requirements are determined and a dynamic model for an industrial vehicle is presented. The model includes a kinematic description of the suspension, a flexible tire-ground interaction model for various ground surface profiles and supports trailer coupling forces with coupling backlash. Simulations of exemplary scenarios are used to verify the proposed vehicle model.